Complement System in the Pathogenesis of Benign Lymphoepithelial Lesions of the Lacrimal Gland. - Jing Li; Xin Ge; Xiaona Wang; Xiao Liu; Jianmin Ma (PLoS ONE, 2016)
We aimed to examine the potential involvement of local complement system gene expression in the pathogenesis of benign lymphoepithelial lesions (BLEL) of the lacrimal gland.We collected data from 9 consecutive pathologically confirmed patients with BLEL of the lacrimal gland and 9 cases with orbital cavernous hemangioma as a control group, and adopted whole genome microarray to screen complement system-related differential genes, followed by RT-PCR verification and in-depth enrichment analysis (Gene Ontology analysis) of the gene sets.The expression of 14 complement system-related genes in the pathologic tissue, including C2, C3, ITGB2, CR2, C1QB, CR1, ITGAX, CFP, C1QA, C4B|C4A, FANCA, C1QC, C3AR1 and CFHR4, were significantly upregulated while 7 other complement system-related genes, C5, CFI, CFHR1|CFH, CFH, CD55, CR1L and CFD were significantly downregulated in the lacrimal glands of BLEL patients. The microarray results were consistent with RT-PCR analysis results. Immunohistochemistry analysis of C3c and C1q complement component proteins in the resected tissue were positive in BLEL patients, while the control group had negative expression of these proteins. Gene ontology (GO) analysis revealed that activation of the genes of complement system-mediated signaling pathways were the most enriched differential gene group in BLEL patients.Local expression of complement components is prominently abnormal in BLEL, and may well play a role in its pathogenesis.